Prevalence & Risk Factors of Post-traumatic Stress Disorder in Patients with Lower Limb Fractures in South Africa - Gerald Tan, MBBS, MRCS, MSc; Maritz Laubscher, MBChB, FC Orth (SA), MMed; Sithombo Maqungo, MBChB, FC Ortho (SA), MMed; Adam Truss, MBChB, BSc (Hons), MRCS; Kirsty Berry, BSc, MBBCh, FC Orth(SA); Nando Ferreira, BSc, MBChB, FC (Orth), MMed, PhD; Simon Matthew Graham, MBChB, MRCS, MSc (Res), FRCS (Orth), PhD (JBJS Open Access)
Background:. Fractures occur at disproportionately higher rates in low-income and middle-income countries (LMIC) and commonly occur following a traumatic event. The association between suffering from a fracture and the development of psychological symptoms is under-reported. The aim of this study was to investigate the prevalence and risk factors of developing post-traumatic stress disorder (PTSD) among patients following lower limb trauma in South Africa. Methods:. The study was undertaken from September 2017 to December 2018 and included a cohort of 260 patients with lower limb long bone fractures. Patients were screened using the Primary Care PTSD (PC-PTSD-5) screening tool, which is a gold standard measure to identify patients at risk of PTSD in the civilian population. Within this cohort, high-risk patients were assessed with the PTSD checklist (PCL-C), which is a standardized questionnaire scale to indicate if an individual may have PTSD. Results:. There were 254 patients in the final cohort analysis with ages ranging from 18 to 71 years, and 75.6% (192/254) of the cohort were male patients. Femoral fractures were found in 51.6% (131/254) of patients while tibial fractures were found in 48.4% (123/254). The rate of PTSD within the study population was found to be 7.1% (18/254), and the risk of developing PTSD was 13.4% (34/254). We did not identify any risk factors, including open fractures, high-injury severity, and complication such as nonunion, for the development of PTSD. Conclusions:. This study found the rate of PTSD to be lower compared with that in high-income countries, but still higher than the general population in South Africa. Our study indicates that screening for PTSD in patients with lower limb trauma in LMICs could be beneficial. Early identification of patients at risk of developing PTSD would enable appropriate resources, support, and treatment to be provided. Level of Evidence:. Level II. See Instructions for Authors for a complete description of levels of evidence.